Learning behavior of technical students – Awareness as key competence - Lackner, Maximilian; Klamert-Schmid, Judith; Zangl, Sabine; Neussner, Wolfgang; Lembacher, Harald; Lutz, Markus (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Learning has become more important than ever before, as we are moving towards a digital, fast-changing society. Formal university training has changed, too, from pure “lectures” to more modern formats, including e-learning, interactive and collaborative settings. Students also find plenty of information online, and the new skill in demand is finding relevant knowledge instead of having memorized knowledge. Knowledge doubles fast and becomes outdated even faster. Being aware of one’s learning behaviors was found to be a core competence of university students eager to educate themselves. This work sets a self-assessment amongst bachelor and master students of a technical programme – International Business and Engineering – into perspective with literature findings. The authors conclude that knowing ones strengths in learning is a prerequisite of acquiring additional knowledge effectively and efficiency. Students have become more demanding towards the presentation of learning opportunities. However, it is them who have to take initiative to make most out of their learning journeys. As students progress through their studies, their awareness of collaborative and interactive learning seems to decrease, which reminds one of Socrates: “The more I know, the more I realize I know nothing.” One can speculate that his finding is due to more critical reflection by master students, or that by the time the students have entered the master’s programme, the novel learning approaches have been familiarized/assimilated and do not receive further attention, which is a hint that the art of collaborative interactive learning has been mastered.